GPS Tracking System for Low Maintenance Application - Hazizulden, Abd Aziz; Nik Mohd Kamil, Nik Yusof; M. H., Abu Talip (2010)
A GPS tracking system utilizing the license-free RF communication is proposed as viable alternative to using the available GSM network for low-cost maintenance. The proposed system is designed based on the popular 8-bit embedded system. It consists of a monitoring unit and a remote unit.Each unit is equipped with, among others, a GPS receiver and an RF transceiver as main components. While there is a need for the remote unit to be small and compact, the monitoring unit is also designed as a portable device. Prototypes are built for design verification. Initial functionality test shows that the system is capable of tracking mobile object not only in outdoor but also in indoor environment.